Sustainability in Knowledge, Attitude, and Practice of COVID-19 Prevention and Control - Lamichhane, Bishnu; Lamichhane, Barha (AMC Journal (Dhangadhi), 2024)
This study assessed the coronavirus disease (COVID-19) related knowledge, attitudes, and practices among residents of Nepal during non-pandemic periods. A total of 204 participants took part in the study. The results revealed that 93.6% of participants could identify the major clinical symptoms of COVID-19. Overall, Nepali residents showed good knowledge and attitudes towards COVID-19, but there is room for improvement in their practices. Stakeholders, local governance, and development agencies should focus on promoting and supporting practices to enhance future pandemic control efforts.